Managerial communication - Bell, Reginald L.; Martin, Jeanette S. (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2014)
Explores what the communication managers actually do in business across the planning, organizing, leading, and controlling functions. The top, middle, and frontline communications in which managers engage is also discussed. All of the levels of communication (intrapersonal, interpersonal, group, organizational, and intercultural) play a role in managerial communication; therefore, these levels are explained thoroughly in Chapter 2, but are relevant in all chapters. As we expound, for example, on theories of communication we relate them to the theories of management such as crisis management, impression management, equity theory, and effective presentation skills. These are the skills that are invaluable to management; you will begin to appreciate the depth and breadth of the painstaking effort we took to explicate these important topics. Our book, therefore, brings communication to the forefront of management theory because it is our belief that management cannot function without the particular techniques of communication covered in Managerial Communication.
1. The nature of managerial communication -- 2. The managerial communication process -- 3. Power, climate, and culture -- 4. Ethical issues in management communication -- 5. Conflict resolution -- 6. Communication technology -- 7. Effective presentation skills -- 8. Impression management -- 9. Employment communication -- 10. Change communication -- 11. Crisis communication -- 12. Communication audits -- About the authors -- References -- Index.
Part of: 2014 digital library.
Includes bibliographical references (pages 233-245) and index.
Title from PDF title page (viewed on September 26, 2014).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Communication in management; business administration; communication; management functions; principles; Electronic books